PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN SEJARAH DI SMA NEGERI 8 PALEMBANG - Apriana Apriana Apriana; Sri Mulyati (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
The reality on the ground shows that most students often feel bored, lazy, sleepy, and bored with history lessons. Therefore, this study aims to determine the Effect of Mind Mapping Learning Model on Student Learning Outcomes in Historical Subjects at SMA Negeri 8 Palembang